2007
DOI: 10.1080/15459620701389909
|View full text |Cite
|
Sign up to set email alerts
|

Mold Contamination and Air Handling Units

Abstract: An investigation was conducted on selected locations in air handling units (AHUs) to (a) identify common mold species found on these locations, (b) determine whether some locations (and subsets) featured mold growth sites more frequently than others, (c) ascertain whether the operating condition of AHUs is related to mold contamination, and (d) provide a basis for a microbial sampling protocol for AHUs. A total of 566 tape lifts and 570 swab samples were collected from the blower wheel fan blades, insulation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 8 publications
1
33
0
Order By: Relevance
“…4) or office environment but also in automobiles, trains and other modern means of transportation. In particular, heating, ventilation and air-conditioning systems tend to foster fungal and bacterial contamination [23,24]. It has been reported that dust in the home environment also carries the potential for Cryptococcus contamination and subsequent exposure risk as high as 13% [21].…”
Section: Discussionmentioning
confidence: 99%
“…4) or office environment but also in automobiles, trains and other modern means of transportation. In particular, heating, ventilation and air-conditioning systems tend to foster fungal and bacterial contamination [23,24]. It has been reported that dust in the home environment also carries the potential for Cryptococcus contamination and subsequent exposure risk as high as 13% [21].…”
Section: Discussionmentioning
confidence: 99%
“…In mechanically ventilated buildings, the system contributes on the contrary [15] most especially the Air Handling Units (AHU) which in its distribution of the conditioned air to the downstream possess potential to circulate mould spores throughout a structure thereby support mould growth. In addition, indoor hygrothermal fluctuations due to inadequate ventilation over a long periods of time results in faster deposition of spores on the material surfaces.…”
Section: Mould and Ventilation Systemsmentioning
confidence: 99%
“…Previous studies exist on investigating the relationship between indoor mould exposure and health related issues [9][10][11][12] but no conclusive evidence exists [13,14]. This according to [15] is as a result of the difficulty in the determination of health risks due to mould exposure and that human responses are a function of a number of factors: types of moulds, the degree and length of exposure, previous history of exposure, and immune status.…”
Section: Introductionmentioning
confidence: 99%
“…In health care buildings, ventilation systems are expected to preventing cross infection risks in addition to maintaining adequate thermal comfort to the patients, the caregivers and visitors. On the contrary, despite the high energy requirements [1,2], the HVAC contributes to making building unhealthy [3] as several cases of nosocomial or hospital acquired illness (HAI) had been previously reported [4][5][6]. These problems, amongst others, had hitherto led to the emergence of building performance diagnostics.…”
Section: Introductionmentioning
confidence: 99%